Effects of shade and chromium propionate supplementation during gestation of beef cows under heat stress: cow thermotolerance, cow–calf performance, and physiological responses - Ferreira, Matheus L; Vedovatto, Marcelo; Siqueira, Isabelle P.; Marcon, Hiam [UNESP]; dos Reis, Bárbara R; Silva, Ronaldo G; Chinaglia, João V; Renno, Luciana N; Edwards, Ashley K (Oxford University Press (OUP), 2025)
This study evaluated the effects of providing or not providing maternal access to shade and chromium (Cr) propionate supplementation for beef cows under heat stress conditions on cow-calf performance, thermotolerance, and physiological responses. Seventy-two Angus-cross cows were stratified by body weight (BW; 566 ± 5.38 kg) and body condition score (BCS; 6.3 ± 0.5) and allocated to 1 of 12 bermudagrass pastures (3 to 5 ha pastures/5 to 7 cows per pasture). Treatments were randomly assigned to pastures in a 2 × 2 factorial arrangement: shade and Cr (SCr), no shade and Cr (NSCr), shade and no Cr (SNCr) and no shade and no Cr (NSNCr), from day 0 to 180 (on average 150 ± 20 d prepartum and 30 ± 10 d post-partum). Chromium propionate was added to the mineral mix at a rate of 1.8% of the total mineral mixture on a weight basis (Cr target intake of 6.3 mg/cow/d). Data was analyzed on SAS as a 2 × 2 factorial design with pasture considered the experimental unit. The SCr cows showed greater BW on days 90 and 120 compared to all other treatments (P = 0.04). Shaded cows had greater BCS on days 30, 60, and 120 (P < 0.001). Supplementation of Cr increased Cr liver concentration of cows (P = 0.05), but not in calves (P = 0.14). Calves born from no-shaded cows showed lower vigor score at birth (P < 0.02) and were lighter at birth and weaning (P < 0.001). Shaded cows had reduced respiration rate (RR) on days 45, 75, and 90, but cows supplemented with Cr showed increased RR on these days (P < 0.01). Shade reduced cows' overall body temperature and rectal temperature (P < 0.001). Shade reduced overall intravaginal temperature (IT), but NSCr cows showed the greatest IT from 0900 to 1800 hours between treatments on days 60 and 90 (P ≤ 0.04). No-shade cows tended to have increased glucose concentrations on days 30, 90, and 120 (P < 0.0001), and increased non-esterified fatty acids concentrations on days 90 and 120 (P < 0.01). Cows supplemented with Cr had reduced total proteins, globulins, and creatinine (P ≤ 0.03) and tended to have reduced glucose concentrations (P = 0.10). NSCr cows had greater serum urea N concentrations on days 30 and 60 compared to NSNCr (P < 0.001). Total protein, globulins, and IgG tended to be greater for calves born from shaded cows (P ≤ 0.10). Shade improved dam performance, thermotolerance and calf vigor, immunity, and growth. Chromium enhanced pre- and postpartum BW, but only when shade was provided. Chromium supplementation did not improve thermotolerance but enhanced physiological responses.